‘Spiritual humanism’ within the realm of Christian aesthetics. Toward the meaning and value of our being human within the theological framework of an aesthetics of compassion. - Louw, D. J. (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
In the centre of Vincent Brümmer’s philosophical and spiritual reflection is the quest for the meaning of the Christian faith, outside the parameters of positivistic schematization. This theological sensitivity stands in close connection to the ontological thinking of his promoter A. E. Loen: meaning is a kind of ontic, creational truth closely related to the noetic category of ‘uitgesprokenheid’ (explicit, expressed, pronounced logos). Brümmer himself has identified “Meaning and the Christian Faith” as the meanders of his thinking, thus the attempt to explore these meanders within the framework of a theological anthropology. With reference to man as homo aestheticus and the aesthetics of theopaschitic theology, the aesthetics of passion and compassion is described as divine Beauty. The passio Dei is an exposition of the praxis concept of ta splanchna. In this regard the notion of “bowel categories” describes a practical theology of the intestines which focuses on the dignity of our being human, thus the option for an inclusive ‘spiritual humanism’ within the framework of the ubuntu-communalism of African spiritualities (theologia Africana).